The Effect of CICADA English Youth Magazine on Secondary School Orphans' Vocabulary Mastery - Suliyono Suliyono (Beyond Words, 2022)
The low English vocabulary mastery has caused Baitul Hijrah Orphanage’s orphans poor achievement of English. Regarding the issue, this research was conducted to find a breakthrough to help the orphans’ vocabulary improvement. In term of boosting their vocabulary need, the researcher explored English youth magazine as a media to be used. Thus, this study was aimed to examine and compare between the effects of using English youth magazine and English textbook on students' vocabulary mastery. This study assigned true-experimental research design to test the hypothesized relationship between variables. The sample of this study was 28 orphans at second grade of senior high school that were divided into control and experimental group by systematic sampling method. Data collection was vocabulary test scores results consisted of 100 multiple choice questions. The result showed that the English youth magazine usage as media could significantly improve vocabulary mastery; thus, students who were taught vocabulary using English youth magazine obtained higher scores than those who were taught vocabulary using English textbook. In conclusion, English youth magazine is a teaching aid that can be used to gain the students' vocabulary mastery.